A Bibliography on Writing and Written Language. 3 vols. - Coulmas, Florian; Ehlich, Konrad (1996)
Akkadian writing: 13-15; Cuneiform writing: 81-85; Decipherment: 104-113; Elamitic scripts: 191-192; Hittite scripts: 270-271; Ideograms: 273-275; Persian scripts: 461-462; Sumerian scripts: 656-658; Ugaritic cuneiform writing: 698-699